Current trend in Image Guided Surgery(IGS) - Aboaba, Abdulfattah A.; Hameed, Shihab A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha (IIUM Press, 2011)
Image-guided surgery (IGS)! Computer-aided surgery (CAS) is a technology mostly deployed in minimally invasive operation [1] which involves the use of tracked surgical instruments in real-time, and computer technology to correlate the operative field to preoperative or intra-operative radiological images during surgical intervention. It also encompasses the use of radiological images and software programs for pre-surgical planning, and post operation monitoring, treatment and medication to patients.